Features of Non-Verbal Communication of Children with Intellectual Disabilities and Differences from their Normatively Developing Peers - Zashchirinskaia, Oksana V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aimed to study the specific features of non-verbal communication in children with intellectual disabilities in the dynamics of psychological impact. Background: In the 21st century, in terms of diagnostics and the implementation of psychological influences, the problem of identifying the features of the communication skills of children with intellectual disabilities becomes very significant and urgent. At present, intellectual disabilities are understood as a heterogeneous group of intellectual impairments, different in clinical manifestations, but based on the criterion of a decrease in cognitive development. A comparatively large number of works are devoted to the study of the features of the communication skills of children with intellectual disabilities. However, the research on their non-verbal communication skills is rather small. Method: The experimental research was conducted in three stages – first, the initial level of development of the abilities of recognition, naming and use of various communicative, modal and descriptive-pictorial gestures was measured. Results: After that, for ten lessons with children, the program "Lessons of non-verbal communication at school" was carried out, after which abilities were tested repeatedly. Parents and teachers were also interviewed twice. Conclusion: The study was carried out based on educational institutions outside school hours. The study involved 128 children from 6 schools in St. Petersburg. Non-verbal communication of children with mild mental retardation in comparison with normatively developing peers and with mixed specific psychological disorders is characterised by a lower level of development of cognitive, emotional-personal and behavioural components. Moreover, the most pronounced is the underdevelopment of the cognitive component, which is associated with the peculiarities of the impairment of intelligence. The study also showed that the emotional-personal and behavioural components are at a more preserved level of development in children with intellectual disabilities, which can be interpreted as the compensatory ability of the child's psyche.